Synthesis and characterization of hydrogels containing redox‐responsive 2, 2, 6, 6‐tetramethylpiperidinyloxy methacrylate and thermoresponsive N‐isopropylacrylamide. Issue 11 (25th April 2020) - Khodeir, Miriam; Jia, He; Antoun, Sayed; Friebe, Christian; Schubert, Ulrich S.; Lu, Yan; Van Ruymbeke, Evelyne; Gohy, Jean‐François
Abstract: Smart hydrogels containing 2, 2, 6, 6‐tetramethylpiperidinoxy methacrylate (TEMPO) and N ‐isopropylacrylamide (NIPAM) that undergo reversible redox behavior are prepared and investigated. Several polymer networks are first prepared by free‐radical copolymerization of varying amounts of TEMPO, NIPAM, and a crosslinker (diethylene glycol diacrylate) and subsequently swelled with water to lead to hydrogels. In order to investigate the effects of the redox activity of TEMPO units and of the lower critical solution temperature of NIPAM on the hydrogel properties, a study of the swelling ratio of the polymer networks in distilled water at different temperatures is performed for the two forms of TEMPO, the reduced (TEMPO) and oxidized (TEMPO + ) one. Moreover, the rheological properties are also measured for both hydrogel forms. Finally, the encapsulation abilities of the oxidized hydrogels are demonstrated via electrostatic interactions between positively charged TEMPO + units and negatively charged guest molecules, supporting future application of our system in the biomedical and environmental fields. Abstract : Hydrogels based on redox‐responsive 2, 2, 6, 6‐tetramethylpiperidinoxy methacrylate (TEMPO), temperature‐responsive N ‐isopropylacrylamide and a diacrylate crosslinker are studied. Due to different reactivity ratios of those comonomers, hydrophobic TEMPO‐rich segments are formed first that aggregate into micellar or nanogel particles, and then can be crosslinked at a higher concentration of the crosslinker, ultimately leading to macroscopic hydrogels. These hydrogels exhibit rich stimuli‐responsive behavior, which is reflected in their temperature and redox responding mechanical properties.